Smoking Kills, Obesity Disables: A Multistate Approach of the US Health and Retirement Survey - Reuser, Mieke; Bonneaux, Luc G; Willekens, Frans J (Obesity (Silver Spring, Md.), 2009)
Increasing BMI causes concerns about the consequences for health care. Decreasing cardiovascular mortality has lowered obesity‐related mortality, extending duration of disability. We hypothesized increased duration of disability among overweight and obese individuals. We estimated age‐, risk‐, and state‐dependent probabilities of activities of daily living (ADL) disability and death and calculated multistate life tables, resulting in the comprehensive measure of life years with and without ADL disability. We used prospective data of 16,176 white adults of the Health and Retirement Survey (HRS). Exposures were self‐reported BMI and for comparison smoking status and levels of education. Outcomes were years to live with and without ADL disability at age 55. The reference categories were high normal weight (BMI: 23–24.9), nonsmoking and high education. Mild obesity (BMI: 30–34.9) did not change total life expectancy (LE) but exchanged disabled for disability‐free years. Mild obesity decreased disability‐free LE with 2.7 (95% confidence limits 1.2; 3.2) year but increased LE with disability with 2.0 (0.6; 3.4) years among men. Among women, BMI of 30 to 34.9 decreased disability‐free LE with 3.6 (2.1; 5.1) year but increased LE with disability with 3.2 (1.6;4.8) years. Overweight (BMI: 25–29.9) increases LE with disability for women only, by 2.1 (0.8; 3.3) years). Smoking compressed disability by high mortality. Smoking decreased LE with 7.2 years, and LE with disability with 1.3 (0.5; 2.5) years (men) and 1.4 (0.3; 2.6) years (women). A lower education decreased disability‐free life, but not duration of ADL disability. In the aging baby boom, higher BMI will further increase care dependence.